THE SOIL AT SITE LARANJEIRAS/QUIPAPÁ - PE, EXTREMELY DEGRADED - Francisco de Moura Júnior, José (Journal of Interdisciplinary Debates, 2023)
Sítio Laranjeiras, is part of the municipality of Quipapá PE, in this place, many years ago farmers explored the region, devastated the local forests, destroyed most of the native vegetation, today what remains of vegetation in this place is just a small forest, the farmers in that region were mostly people, people who didn’t even have elementary school, some knew how to write only their name, others not even that. Currently the correct management of the soil is studied by numerous scientists and scholars in the area of sustainability, these scholars and the like see every day more acting for a correct use of the soil. Looking for ways to plant and not cause so much erosion. Due to lack of important knowledge, the farmers in the studied area practically destroyed the soil, currently there are no more cassava crops and others that before were quite common in the place.